Neutrophilia and mortality in women with uterine carcinosarcoma. Issue 8 (17th July 2019) - Arend, Rebecca; Van Arsdale, Anne; Gojayev, Anar; Roane, Brandon Michael; Doo, David; Leath, Charles; Goldberg, Gary L; Huang, Gloria
Abstract : Objective: The objective of this study was to investigate the relationship between pre-treatment absolute neutrophil count and clinical outcomes in patients with uterine carcinosarcoma. Methods: In an Institutional Review Board approved, retrospective cohort study of 103 patients with uterine carcinosarcoma, the pre-treatment absolute neutrophil count data were obtained from the medical records, along with clinical, pathologic, treatment, and outcome data. Kaplan–Meier survival estimates were calculated and compared by the log rank test. Univariable and multivariable Cox proportional hazard regression models were used to examine the relationship of pre-treatment absolute neutrophil count with progression-free survival and overall survival. Results: Uterine carcinosarcoma patients in the highest quartile of pre-treatment absolute neutrophil count had significantly reduced progression-free survival (p<0.001, log rank test), and overall survival (p<0.001, log rank test), compared with patients in the lower absolute neutrophil count quartiles. On multivariable analysis, high absolute neutrophil count was an independent poor prognostic factor for disease recurrence, HR 2.97 (95% CI 1.35 to 6.53, p=0.007) for highest versus lowest quartile absolute neutrophil count, and for mortality, HR 4.43 (95% CI 1.64 to 12.00, p= 0.003). Conclusions: High pre-treatment absolute neutrophil count is an independent poor prognostic factor in patients with uterine carcinosarcoma and may be useful as a potential biomarker in clinical trials. The mechanistic relationship of neutrophilia and uterine carcinosarcoma progression merits further investigation.